2011
DOI: 10.1007/s00441-011-1266-7
|View full text |Cite
|
Sign up to set email alerts
|

Development of the zebrafish myoseptum with emphasis on the myotendinous junction

Abstract: Zebrafish myosepta connect two adjacent muscle cells and transmit muscular forces to axial structures during swimming via the myotendinous junction (MTJ). The MTJ establishes transmembrane linkages system consisting of extracellular matrix molecules (ECM) surrounding the basement membrane, cytoskeletal elements anchored to sarcolema, and all intermediate proteins that link ECM to actin filaments. Using a series of zebrafish specimens aged between 24 h post-fertilization and 2 years old, the present paper descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 39 publications
(50 reference statements)
2
75
0
2
Order By: Relevance
“…It has been demonstrated that the horizontal myosepta, which separate the epaxial and hypaxial musculature, are derived from the myotomal muscle pioneer cells (Devoto et al, 1996;Felsenfeld et al, 1991;Hatta et al, 1991;Schweitzer et al, 2005). By contrast, the vertical myosepta are believed to be of sclerotomal origin, making them analogous to mammalian axial tendon tissue (Bricard et al, 2014;Charvet et al, 2011). In the developing somite of zebrafish, which comprises predominantly myotomal cells, the sclerotomal cells form in the ventralmost domain and migrate dorsally to eventually surround the notochord and neural tube (Morin-Kensicki and Eisen, 1997; Stickney et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the horizontal myosepta, which separate the epaxial and hypaxial musculature, are derived from the myotomal muscle pioneer cells (Devoto et al, 1996;Felsenfeld et al, 1991;Hatta et al, 1991;Schweitzer et al, 2005). By contrast, the vertical myosepta are believed to be of sclerotomal origin, making them analogous to mammalian axial tendon tissue (Bricard et al, 2014;Charvet et al, 2011). In the developing somite of zebrafish, which comprises predominantly myotomal cells, the sclerotomal cells form in the ventralmost domain and migrate dorsally to eventually surround the notochord and neural tube (Morin-Kensicki and Eisen, 1997; Stickney et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…TPCs only appear later along the ISBs, where they contribute additional ECM to strengthen existing attachments in what we refer to here as a 'tendon-dependent' phase ( Fig. 3B) (Charvet et al, 2011Chen and Galloway, 2014;Subramanian and Schilling, 2014). Thus, in zebrafish, somitic muscles attach via the myomatrix at ISBs prior to the appearance of TPCs.…”
Section: Ecm Production and Function During Tenocyte Morphogenesis Anmentioning
confidence: 93%
“…Studies of FACITs at zebrafish ISBs have been informative for understanding their functions as MTJs mature. In zebrafish, muscles first express Col12a1 and Col22a1 at larval stages and these progressively align into the orthogonal fibril arrays of mature MTJ/tendon ECM (Charvet et al, 2011. Col12a1 is expressed earlier than Col22a1 and colocalizes with Lama2 throughout muscle fiber attachment ).…”
Section: Ecm and Collagen Fibril Assembly During Tendon And Mtj Maturmentioning
confidence: 99%
“…Like tendons in amniotes, fish myosepta serve as transmitters of muscle contractility to bones. In the developing fish embryo, the myosepta are initially acellular and composed of matricial compounds such as fibronectin, laminin and collagens (Henry et al, 2005;Charvet et al, 2011;Bricard et al, 2014 ent in the intersomitic space (Charvet et al, 2011;Bricard et al, 2014;Chen and Galloway., 2014;Subramanian and Schilling., 2014). These myoseptal cells are considered homologous to axial tenocytes in amniotes: they express scleraxis, tenomodulin and tendon associated collagens (Bricard et al, 2014;Chen and Galloway, 2014) and, like axial tenocytes in amniotes (Brent et al, 2003), they probably originate from a somite-derived syndetome compartment (Bricard et al, 2014;Chen and Galloway, 2014;Subramanian and Schilling, 2014).…”
Section: Abstract: Cilp1 Somite Myotome Dermomyotome Myoseptal Cmentioning
confidence: 99%
“…Like tendons in amniotes, fish myosepta serve as transmitters of muscle contractility to bones. In the developing fish embryo, the myosepta are initially acellular and composed of matricial compounds such as fibronectin, laminin and collagens (Henry et al, 2005;Charvet et al, 2011;Bricard et al, 2014). After somitogenesis, myoseptal cells become appar-ent in the intersomitic space (Charvet et al, 2011;Bricard et al, 2014;Chen and Galloway., 2014;Subramanian and Schilling., 2014).…”
mentioning
confidence: 99%